Bankruptcy Petition Based on Debt Arising from Agreement with Arbitration Clause - Gunawan, Triandy; Rachman, Yulian Ananto (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
The business world requires efficient and cost-effective methods of resolving business disputes. With the presence of Arbitration Institutions as an alternative for resolving business disputes outside the judicial system, the business world has various options tailored to their characteristics and needs. Apart from going through arbitration institutions, it turns out that debt dispute resolution can also be done through PKPU (Postponement of Debt Payment Obligations) and filing for Bankruptcy at the Commercial Court. The disharmony between the absolute authority of arbitration which is extra-judicial in nature and the absolute authority of the Commercial Court which is an extraordinary court in examining and adjudicating bankruptcy applications gives rise to legal problems which can affect the confidence of the business world. This research aims to analyze bankruptcy applications based on debts arising from agreements with arbitration clauses. This research uses normative legal research methods with a statutory approach and a legal concept analysis approach. The research results show that the Commercial Court is an extraordinary court, so it has the authority to adjudicate bankruptcy applications even though there is an arbitration clause. To file a bankruptcy petition at the Commercial Court, it is necessary to fulfill the requirements of simple proof of the existence of at least two creditors, one of whose debts is due and can be collected.